2017
DOI: 10.15760/trec.178
|View full text |Cite
|
Sign up to set email alerts
|

mpacts of Bus Rapid Transit (BRT) on Surrounding Residential Property Values

Abstract: Type of Report and Period Covered Sponsoring Agency Code Supplementary Notes AbstractAs bus rapid transit (BRT) grows in popularity in the United States, a better understanding of the mode's impacts on land uses and property values is needed. Economic theory suggests, and literature has shown, that people are willing to pay higher housing costs to lower their costs of transportation to areas of economic activity. Does high-quality BRT service reliably provide such access and, thereby, increase residential prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…Mobility-limiting strategies (e.g., tolls, gas taxes, and parking pricing) may reduce emissions at the urban scale, but may also be increasingly burdensome to low-income individuals in cities where walkable, mixed-use, highly accessible neighborhoods are not affordable. Urban areas that propose mobility-enhancing strategies (e.g., certain types of fixed guideway transit expansion) to connect workers to the labor market may risk increasing residential land values along transit lines ( 43 47 ) and unintentionally evict low-income residents. More research is needed on how publicly and privately funded climate mitigation efforts that increase accessibility affect housing markets and municipal goals for social equity.…”
Section: Discussionmentioning
confidence: 99%
“…Mobility-limiting strategies (e.g., tolls, gas taxes, and parking pricing) may reduce emissions at the urban scale, but may also be increasingly burdensome to low-income individuals in cities where walkable, mixed-use, highly accessible neighborhoods are not affordable. Urban areas that propose mobility-enhancing strategies (e.g., certain types of fixed guideway transit expansion) to connect workers to the labor market may risk increasing residential land values along transit lines ( 43 47 ) and unintentionally evict low-income residents. More research is needed on how publicly and privately funded climate mitigation efforts that increase accessibility affect housing markets and municipal goals for social equity.…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that local contexts, such as social factors (habits) and planning policy play an important role in the impact of new transit projects. It should also be noted, that although there is evidence of uniform impacts that rapid transit has on housing prices across the globe (Perk et al, 2017), for this review the authors intentionally focused on the US, Canada, and other countries with a comparable institutional and economic setting (i.e., democratic countries with a high level of economic development, where the planning and delivery of transit services follow a similar institutional framework), to understand where the study fits among research efforts with a similar context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De acordo com a Administração Federal de Trânsito (AFT), é um sistema de trânsito que pode incluir prioridade de semáforos, plataformas elevadas e estações melhoradas (V. Perk, Catalá, Mantius, & Corcoran, 2017). O consideram um sistema de tráfego de ônibus bastante complexo, porque envolve a circulação de ônibus em ônibus especialmente designados e, muitas vezes, em faixas de tráfego cercadas (Sakhno et al, 2019).…”
Section: Sistema De Trânsito Rápido De ôNibus (Brt)unclassified
“…Importante observar que, para ser considerado BRT, o serviço deve incorporar alguma forma de cada um desses sete elementos. Serviços típicos de paradas limitadas ou serviços de ônibus expresso não são considerados BRT (V. Perk et al, 2017).…”
Section: Característicasunclassified
See 1 more Smart Citation